DINAMIKA PRASANGKA SOSIAL PENYEBARAN AGAMA TERHADAP PIHAK RUMAH KHALWAT OASIS SUNGAI KERIT - Musmuallim Musmuallim (al-Balagh : Jurnal Dakwah dan Komunikasi, 2019)
Oasis Sungai Kerit (OSK) is a hermitage or khalwat house as a place of worship rituals and prayer services for Catholics in Melung Village, Kedungbanteng, Banyumas. Its existence is considered to spread religion and cause unrest. This study elaborates on the dynamics of the emergence of prejudices against OSK managers and formulates suggestions for these problems through a phenomenological approach. Data collection is done by interviews and documentation that are arranged and presented descriptively. In this study it was concluded that 1) Prejudice of the spread of Catholicism by the OSK khalwat house was due to the categorization and ingroup-outgroups, 2) Prejudice also occurred because there were OSK khalwat house activities in accordance with prejudice, 3) Problems of licensing strengthened community rejection. Dialogue efforts have been made but not yet optimal. Therefore, it is necessary to reorganize the format of dialogue between various parties so that dialogue can take place openly and intensively so that prejudice can be reduced.